Analysis of Hemichannels and Gap Junctions: Application and Extension of the Passive Transmembrane Ion Transport Model - Wang, Qiqian; Liu, Shenquan (Frontiers in Cellular Neuroscience, 2021)
Electrical synaptic transmission is an essential form of interneuronal communication, which is mediated by clusters of intercellular channels assembled as gap junctions that allow the passage of ions. Three gene families (connexins, innexins, and pannexins) have evolved to form gap junctional channels. Each gap junctional channel is formed by the docking of a hemichannel in the membrane of one cell with a corresponding hemichannel in the membrane of an adjacent cell. To date, there has been a lack of models describing this structure in detail. In this study, we demonstrate that numerical simulations suggest that the passive transmembrane ion transport model, which is based on the generality of ion channels, also applies to hemichannels in non-junctional plasma membranes. On this basis, we established a gap junctional channel model, which describes the docking of hemichannels. We simulated the homotypic and heterotypic gap junctions formed by connexins, innexins, and pannexins. Based on the numerical results, we discussed the physiology of hemichannels and gap junctions, such as ion blockage of hemichannels, voltage gating of gap junctions, and asymmetry and delay of electrical synaptic transmission, for which the numerical simulations are first comprehensively realised, and provided explanations based on our model.